A Comparative Evaluation of TiO 2 Suspension Coating Techniques: A Novel Technique to Achieve Optimal Thickness and Uniformity of Photocatalytic Film. (13th December 2012) - Rismanchian, Masoud; Golbabaei, Farideh; Mortazavi, Yadollah; Pourtaghi, Gholamhossein; Rahimi Foroushani, Abbas; Nassiri, Parvin
Abstract : The most important parameters affecting the efficiency of catalysts for the oxidation of the surrounding materials are considered to be the thickness and uniformity of the catalyst layer. The present method for the determination of thickness used in most studies is the analysis of cross-sectional pictures from SEM imaging. This method, however, has several restrictions. This study proposes a feasible and simple method for evaluating the optimal thickness and uniformity using UVA light transmitted through the samples. Three techniques for catalyst deposition have been investigated in this study using UVA light transmitted through the samples and by measuring the photocatalytic activity. These methods include lowering, dip coating, and spraying, which showed coefficients of variation for the coated catalyst weight of 28.4%, 13.6%, and 3.24%, respectively. The samples from the lowering, dip coating, and spraying techniques showed UVA transmissions of 95.02%, 68.8%, and 15.6%, respectively. The spraying technique displayed the lowest values for both. The estimated removal efficiencies (%RE/mg· cm −2 ) for lowering, dip coating, and spraying were 18.42, 16.84, and 24.15, respectively. Using these analyses it was determined that the spraying technique yielded the best photocatalytic oxidation performance of the three techniques studied.